SISTEM BAGI HASIL PADA USAHATANI PADI SAWAH DI KECAMATAN LANGOWAN UTARA - Andre Rolef Bawohan; Theodora Maulina Katiandagho; Mex Frans Lodwyk Sondakh (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study was to determine the profit sharing system between land owners and tenants in Langowan Utara Sub-District. This research was conducted for three months at Langowan Utara District from November 2020 to January 2021. The data used in this study are primary data which is processed based on interviews with 15 tenant farmer respondents who were taken intentionally and secondary data were obtained from the village office and sub-district office and literature in libraries and on the internet related to this research. The method used in this research is descriptive method. The results showed that the sharing of agricultural land in the village was carried out with a system of three or 1:2, the division was that the tenant farmers got two parts and the owner farmers got one share, the provision of seeds, fertilizers, labor, etc. until the harvest period is borne by the cultivator while the owner farmer only receives the net harvest without paying any fees.